Perceptions of colorectal cancer screening in the Arab American community: a pilot study. (2019) - Alsayid, Muhammad; Tlimat, Nour Mazen; Spigner, Clarence; Dimaano, Christian
Abstract: Objective: Multiple factors such as socioeconomic status (SES), education, race, and ethnicity can affect colorectal cancer screening (CRCS) rates. However, few studies have addressed CRCS disparities among Arab Americans. Our aim was to understand how Arab Americans view CRCS. Method: Employing thematic analysis, we collected and analyzed the dialogue of Arab American focus groups and interviews to better understand participants' perceptions of CRCS. Themes were generated and categorized into barriers and facilitators. Results: Eleven Arab American males participated in two focus groups and two interviews. Three barriers included disbelief in modern medicine, concerns about the procedure, and lack of communication with the physician. Three facilitators were also identified: compliance and priority of health, access to healthcare, and awareness. Conclusion: Disparities in CRCS cannot solely be explained by SES and access but cultural differences also contribute. Specific interventions accounting for these cultural differences are needed to reduce disparities in CRCS among Arab Americans.